2020
DOI: 10.1111/ans.15712
|View full text |Cite
|
Sign up to set email alerts
|

Trends in knee magnetic resonance imaging, arthroscopies and joint replacements in older Australians: still too much low‐value care?

Abstract: Background: The objective of the study is to describe temporal trends and regional variations in the use of knee magnetic resonance imaging (MRI), knee arthroscopy and total knee replacement surgery in Australians older than 55 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…This increase aligns with findings using Medicare Benefits Scheme claims data in Australians aged over 55 years. 19 Thus GP education should emphasise that imaging in OA should be reserved for cases where a differential diagnosis needs to be excluded or if joint replacement surgery is being considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This increase aligns with findings using Medicare Benefits Scheme claims data in Australians aged over 55 years. 19 Thus GP education should emphasise that imaging in OA should be reserved for cases where a differential diagnosis needs to be excluded or if joint replacement surgery is being considered.…”
Section: Discussionmentioning
confidence: 99%
“…Temporal trends reported in a retrospective study using Australian Medicare Benefits Scheme claims data from 2003 to 2017 showed that knee arthroscopy rates increased from 2003 before declining modestly from 2011, likely due to accumulating evidence that did not support its ongoing use, 20 while joint replacement rates have continued to increase. 19 GP referrals to orthopaedic surgeons remained more than double those to allied health professionals.…”
Section: Discussionmentioning
confidence: 99%
“…The authors highlight the absence of good data on the size of the candidate population without which it may be difficult to decide on what should be the appropriate rate of procedures. Nevertheless, up to 10-fold variation in rates between different parts of the country suggests a very patchy response within a single healthcare system, a finding that studies in Australia 90 and France 91 appear to support.…”
Section: When Less Is More? Deprescribing and Decommissioningmentioning
confidence: 95%
“…The results are presented in Fig. 2 [ 20 23 , 26 29 , 35 , 40 42 , 54 , 64 , 68 , 69 , 122 , 123 , 125 , 127 – 130 , 140 , 141 , 143 , 145 147 , 157 159 , 172 174 , 176 , 177 , 179 , 182 , 190 , 210 , 211 , 213 , 215 , 216 , 229 , 242 , 252 , 277 , 284 , 353 387 ]. From these studies, imaging examinations with a high proportion of low-value examinations (more than 50% inappropriate use reported) was: Head CT (routine and repeat), routine trauma scan, MRI in musculoskeletal pain, dual-energy x-ray absorptiometry (DEXA) in low risk patients or low interval DEXA follow-ups, echocardiography, carotid imaging, chest X-ray, X-ray in acute rhinosinusitis, CTA in pulmonary embolism, early-stage breast cancer staging, acute pancreatitis, and special imaging for pre-op templar bone CT in cochlear implantation, and CT/MRI in long bone cartilaginous lesions.…”
Section: The Quantity In Use Of Low-value Examinationsmentioning
confidence: 99%